PENINGKATAN KETERAMPILAN MENULIS PARAGRAF DESKRIPSI DENGAN TEKNIK OBYEK LANGSUNG MELALUI PENDEKATAN KONTEKSTUAL BERBASIS PEMODELAN - Purwanto, Rahmat (Jurnal Inovasi Pembelajaran Karakter, 2022)
Student learning outcomes in writing descriptive paragraphs at SDN Tlogopandogan 2 are still relatively low, students' ability to write is still very limited, moreover to be able to write descriptive paragraphs they have difficulty being able to distinguish the types of paragraphs. In order to be able to write sometimes students need to be encouraged by using interesting techniques and media. For this reason, so that the learning carried out can run optimally, action is needed in the form of applying techniques and approaches in learning to write descriptive paragraphs including using direct object techniques and contextual approaches. This study aims to improve student learning outcomes. The method used is classroom action research which is carried out for two cycles. The results showed that there was an increase from the first cycle (64,00%), and in the second cycle it became (77,67%).